KONDISI USAHA PERIKANAN TANGKAP PASCA GEMPA DI SUMATERA BARAT - Kamal, Eni (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
Earthquake that occurred in the area of West Sumatera, especially the earthquake that occurred repeatedly since 2004 to 2009 has greatly impacted to the progress and development of fishing effort in seven districts that have sea area in West Sumatera. This study aims to assess the marine business conditions after the earthquake in West Sumatra for can be considered to make policy in the management of fishing effort further. Marine fisheries statistics data indicate that there has been a decline in the number of fishermen postearthquake from 2005 to 2009 as 22.49 percent, the decline in capture fisheries production to 16.12 percent and a decrease in the fishing fleet to 23.89 percent. In resource management and development strategies in the field of maritime affairs and fisheries, it is important to make a comprehensive policy after the earthquake in West Sumatra.